2006
DOI: 10.1038/sj.ki.5000299
|View full text |Cite
|
Sign up to set email alerts
|

State-level adjusted ESRD incident rates: Use of observed vs model-predicted category-specific rates

Abstract: Because of differences in case-mix across states, state-level case-mix-adjusted end-stage renal disease (ESRD) incident rates are reported in each United States Renal Data System Annual Data Report to make the across-state comparisons valid. The adjusted rates were estimated by the direct adjustment method, a widely used method for adjusted event rate calculation, based on observed category-specific ESRD incident rates in each state (called the observation-based method). However, when some adjusting categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…The cumulative probability of death during the follow‐up period was estimated by the Kaplan–Meier method; differences were tested using the log‐rank test. The cumulative probability of death was further adjusted for age, sex, race, ESRD duration, ESRD etiology, dialysis modality type at AMI admission, baseline coronary revascularization, and comorbid conditions using a model‐based direct adjustment method with the 2008 cohort as the reference 17. The differences in unadjusted and adjusted cumulative probability of death across cohort years at 1 and 2 years of follow‐up were assessed using the bootstrap method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative probability of death during the follow‐up period was estimated by the Kaplan–Meier method; differences were tested using the log‐rank test. The cumulative probability of death was further adjusted for age, sex, race, ESRD duration, ESRD etiology, dialysis modality type at AMI admission, baseline coronary revascularization, and comorbid conditions using a model‐based direct adjustment method with the 2008 cohort as the reference 17. The differences in unadjusted and adjusted cumulative probability of death across cohort years at 1 and 2 years of follow‐up were assessed using the bootstrap method.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative probability of death was further adjusted for age, sex, race, ESRD duration, ESRD etiology, dialysis modality type at AMI admission, baseline coronary revascularization, and comorbid conditions using a model-based direct adjustment method with the 2008 cohort as the reference. 17 The differences in unadjusted and adjusted cumulative probability of death across cohort years at 1 and 2 years of follow-up were assessed using the bootstrap method. Visual inspection revealed that the proportionality of the risk of death over time across cohort years was questionable, and a piece-wise Cox regression model was used to address the time dependency of risk of death with cutoffs of ≤1 month and >1 to ≤24 months after AMI admission and included factors listed in Table 1.…”
Section: Statistical Methodologymentioning
confidence: 99%
“…An attractive alternative is a model-based approach, in which we find a good model to calculate category-specific estimated rates for each group, and then calculate direct adjusted rates using these estimates with a given reference population. This method can also be extended to adjustments with continuous adjusting variables (Liu et al, 2006). As in previous ADRs, standard errors of the adjusted rates are calculated using a bootstrap approach.…”
Section: Model-based Adjustmentmentioning
confidence: 99%
“…As such, adjusted rates and associated standard errors can be inaccurate or misleading. For this reason, the predicted outcome was directly standardized to patient characteristics from a reference cohort (Q4 2011) [21] . Finally, we evaluated whether the observed changes in each of the quarterly outcomes over time persisted after adjustment for case-mix differences (age, sex, race, dialysis duration, and primary cause of ESRD).…”
Section: Statistical Analysesmentioning
confidence: 99%